Cryptic Diversity and Database Errors Challenge Non-indigenous Species Surveys: An Illustration With Botrylloides spp. in the English Channel and Mediterranean Sea - Viard, Frédérique; Roby, Charlotte; Turon, Xavier; Bouchemousse, Sarah; Bishop, John (Frontiers in Marine Science, 2019)
Molecular tools have been extensively used in recent decades to examine biological invasion processes, and are increasingly being adopted as efficient tools to support non-indigenous species surveys, notably through barcoding approaches, i.e. the use of a reference sequence specific to a given species to validate its identification. The technique is easy to use but requires reliable reference sequences to be available in public databases. In addition, the increasing discovery of cryptic species in marine taxa may complicate taxonomic assignment. We illustrate these two issues in the ascidian genus Botrylloides, in which at least three global marine invaders have been recognized, including B. violaceus and B. diegensis. We obtained COI sequences from >750 colonies of Botrylloides spp. sampled in W Europe or provided by expert colleagues from other regions. Phylogenetic trees clearly distinguished our targeted taxa (i.e. B. violaceus, B. diegensis and B. leachii (native)). They also revealed another discrete lineage apparently related to a recently-described eastern Mediterranean species. By examining public databases, we found sequences of B. diegensis erroneously assigned to B. leachii. This observation has major implications as the introduced B. diegensis can be misidentified as a putatively native species. We also checked published sequences of the genus Botrylloides in the Mediterranean Sea, complemented with new samples. Based on our custom reference database, all published sequences of B. leachii corresponded to B. diegensis, although this NIS has hardly been reported at all in the Mediterranean region. Such database errors are unfortunate, as the barcoding approach is a powerful tool to identify the recognized Botrylloides species currently present in European seas. This is of particular importance because a trait often used during field assessment, i.e. single-color vs two-color colonies, is misleading to distinguish B. violaceus and B. diegensis respectively: a substantial proportion of the single-color morph are actually B. diegensis in both the Mediterranean Sea and the English Channel. Altogether, this study exemplifies the advantages and disadvantages of molecular barcoding in NIS surveys and studies. The limitations that were identified are all easy to resolve once proper vouchers and collections are set up.